From the equation y = 20x, we can find the missing y-value and x-value as follows:
For (3, y):
Substitute x = 3 into the equation y = 20x:
y = 20(3) = 60
Therefore, the y-value is 60.
For (x, 8):
Substitute y = 8 into the equation y = 20x:
8 = 20x
Divide both sides of the equation by 20:
8/20 = x
Simplifying, we have:
0.4 = x
Therefore, the x-value is 0.4.
In summary:
(3, y) = (3, 60)
(x, 8) = (0.4, 8)
Given the equation y=20x, fill in the missing y-value and x-value
(3,y) y=?
(x,8) x=?
find y and x
READ THE EQUATION BEFORE SOLVING
11 answers
Write an equation from slope-intercept form from the table below
x: 0 , -8 , -16 , -24
y: 3 , -4 , -11 , -18
y=?x+?
x: 0 , -8 , -16 , -24
y: 3 , -4 , -11 , -18
y=?x+?
To write the equation in slope-intercept form (y = mx + b), we need to find the values of m (slope) and b (y-intercept).
First, we can use any two points from the table to find the slope (m). Let's use the points (-8, -4) and (-16, -11).
m = (change in y) / (change in x)
m = (-11 - (-4)) / (-16 - (-8))
m = (-11 + 4) / (-16 + 8)
m = -7 / -8
m = 7/8
Now, we can substitute the slope (m) and one of the points into the slope-intercept form to find the y-intercept (b). Let's use the point (-8, -4):
y = mx + b
-4 = (7/8)(-8) + b
-4 = -7 + b
b = -4 + 7
b = 3
Therefore, the equation in slope-intercept form is:
y = (7/8)x + 3
First, we can use any two points from the table to find the slope (m). Let's use the points (-8, -4) and (-16, -11).
m = (change in y) / (change in x)
m = (-11 - (-4)) / (-16 - (-8))
m = (-11 + 4) / (-16 + 8)
m = -7 / -8
m = 7/8
Now, we can substitute the slope (m) and one of the points into the slope-intercept form to find the y-intercept (b). Let's use the point (-8, -4):
y = mx + b
-4 = (7/8)(-8) + b
-4 = -7 + b
b = -4 + 7
b = 3
Therefore, the equation in slope-intercept form is:
y = (7/8)x + 3
Write an equation from slope-intercept form from the table below
x: 2 , 4 , 6
y: 14 , 20 , 26
y=?x+?
x: 2 , 4 , 6
y: 14 , 20 , 26
y=?x+?
To write the equation in slope-intercept form (y = mx + b), we need to find the values of m (slope) and b (y-intercept).
First, we can use any two points from the table to find the slope (m). Let's use the points (2, 14) and (4, 20).
m = (change in y) / (change in x)
m = (20 - 14) / (4 - 2)
m = 6 / 2
m = 3
Now, we can substitute the slope (m) and one of the points into the slope-intercept form to find the y-intercept (b). Let's use the point (2, 14):
y = mx + b
14 = 3(2) + b
14 = 6 + b
b = 14 - 6
b = 8
Therefore, the equation in slope-intercept form is:
y = 3x + 8
First, we can use any two points from the table to find the slope (m). Let's use the points (2, 14) and (4, 20).
m = (change in y) / (change in x)
m = (20 - 14) / (4 - 2)
m = 6 / 2
m = 3
Now, we can substitute the slope (m) and one of the points into the slope-intercept form to find the y-intercept (b). Let's use the point (2, 14):
y = mx + b
14 = 3(2) + b
14 = 6 + b
b = 14 - 6
b = 8
Therefore, the equation in slope-intercept form is:
y = 3x + 8
Write an equation from slope-intercept form from the table below
x: 0 , 8 , 16 , 24
y: 3 , -6 , -15 , -24
y=?x+?
x: 0 , 8 , 16 , 24
y: 3 , -6 , -15 , -24
y=?x+?
To write the equation in slope-intercept form (y = mx + b), we need to find the values of m (slope) and b (y-intercept).
First, we can use any two points from the table to find the slope (m). Let's use the points (8, -6) and (16, -15).
m = (change in y) / (change in x)
m = (-15 - (-6)) / (16 - 8)
m = (-15 + 6) / (16 - 8)
m = -9 / 8
Now, we can substitute the slope (m) and one of the points into the slope-intercept form to find the y-intercept (b). Let's use the point (8, -6):
y = mx + b
-6 = (-9/8)(8) + b
-6 = -9 + b
b = -6 + 9
b = 3
Therefore, the equation in slope-intercept form is:
y = (-9/8)x + 3
First, we can use any two points from the table to find the slope (m). Let's use the points (8, -6) and (16, -15).
m = (change in y) / (change in x)
m = (-15 - (-6)) / (16 - 8)
m = (-15 + 6) / (16 - 8)
m = -9 / 8
Now, we can substitute the slope (m) and one of the points into the slope-intercept form to find the y-intercept (b). Let's use the point (8, -6):
y = mx + b
-6 = (-9/8)(8) + b
-6 = -9 + b
b = -6 + 9
b = 3
Therefore, the equation in slope-intercept form is:
y = (-9/8)x + 3
Find the slope between (8,3) and (5,6)
To find the slope between the points (8,3) and (5,6), we can use the formula:
slope = (change in y) / (change in x)
Let's denote the coordinates of the first point as (x1, y1) = (8,3) and the coordinates of the second point as (x2, y2) = (5,6).
Using the formula, the slope is calculated as:
slope = (y2 - y1) / (x2 - x1)
slope = (6 - 3) / (5 - 8)
slope = 3 / (-3)
slope = -1
Therefore, the slope between the points (8,3) and (5,6) is -1.
slope = (change in y) / (change in x)
Let's denote the coordinates of the first point as (x1, y1) = (8,3) and the coordinates of the second point as (x2, y2) = (5,6).
Using the formula, the slope is calculated as:
slope = (y2 - y1) / (x2 - x1)
slope = (6 - 3) / (5 - 8)
slope = 3 / (-3)
slope = -1
Therefore, the slope between the points (8,3) and (5,6) is -1.
Find the slope between (-5,1) and (4,9)
To find the slope between the points (-5,1) and (4,9), we can use the formula:
slope = (change in y) / (change in x)
Let's denote the coordinates of the first point as (x1, y1) = (-5,1) and the coordinates of the second point as (x2, y2) = (4,9).
Using the formula, the slope is calculated as:
slope = (y2 - y1) / (x2 - x1)
slope = (9 - 1) / (4 - (-5))
slope = 8 / 9
Therefore, the slope between the points (-5,1) and (4,9) is 8/9.
slope = (change in y) / (change in x)
Let's denote the coordinates of the first point as (x1, y1) = (-5,1) and the coordinates of the second point as (x2, y2) = (4,9).
Using the formula, the slope is calculated as:
slope = (y2 - y1) / (x2 - x1)
slope = (9 - 1) / (4 - (-5))
slope = 8 / 9
Therefore, the slope between the points (-5,1) and (4,9) is 8/9.